Retrieval profiling framework for thematic interpretation of Al-Quran - Salahuddin, Ashraf Ali; Othman, Roslina (The Institute of Electrical and Electronics Engineers, Inc., 2016)
A retrieval profiling is to capturing the metadata of search process and the details of retrieval results. According to the theory of information retrieval (IR) that relevance judgment should be justified by user's needs, the aim of this research is to propose a retrieval profiling framework (RPF) for pooling relevant interpretations of al-Quran based on thematic search. A thematic interpretation of al-Quran is called tafseer al-maudu'iy. The domain tafseer al-maudu'iy is sensitive in IR due to its interrelation of Quranic interpretation within its verse(s). On account of this concern, this paper has proposed a RPF to develop a standard procedure for themes/topics of al-Quran in order to keep the interrelation in search. It has undertaken mix methodology with a comparative study on two thematic search engines of al-Quran and two sources of thematic interpretation of al-Quran to accomplish the procedure. With a counting number of themes and experts' justification, it encountered a pilot test to justify the validity of the RPF and found effective. Despite the limitation of data and experts, it is assumed that this RPF can contribute to users in thematic search of al-Quran as well as it can practically guide the IR system developers for generating a good retrieval platform based on thematic search of Quranic interpretation.